Effects of Sucrose and Benzyl Alcohol on GCSF Conformational Dynamics Revealed by Hydrogen Deuterium Exchange Mass Spectrometry. Issue 5 (18th February 2015) - Zhang, Jun; Banks, Douglas D.; He, Feng; Treuheit, Michael J.; Becker, Gerald W.
<x xml:space="preserve">Abstract</x> Protein stability, one of the major concerns for therapeutic protein development, can be optimized during process development by evaluating multiple formulation conditions. This can be a costly and lengthy procedure where different excipients and storage conditions are tested for their impact on protein stability. A better understanding of the effects of different formulation conditions at the molecular level will provide information on the local interactions within the protein leading to a more rational design of stable and efficacious formulations. In this study, we examined the roles of the excipients, sucrose and benzyl alcohol, on the conformational dynamics of recombinant human granulocyte colony stimulating factor using hydrogen/deuterium exchange coupled with mass spectrometry (HDX‐MS). Under physiological pH and temperature, sucrose globally protects the whole molecule from deuterium uptake, whereas benzyl alcohol induces increased deuterium uptake of the regions within the α‐helical bundle, with even larger extent. The HDX experiments described were incorporated a set of internal peptides (Zhang et al., 2012. Anal Chem 84:4942–4949) to monitor the differences in intrinsic exchange rates in different formulations. In addition, we discussed the feasibility of implementing HDX‐MS with these peptide probes in protein formulation development. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1592–1600, 2015